Isotipos IgG e IgM anti-dsDNA em pacientes com lúpus eritematoso sistêmico - Keiserman, Briele (2012)
IgG anti-dsDNA antibodies are associated to lupus nephritis. Recent data suggest that IgM isotype is nephroprotector. We evaluated the frequency of IgG anti-dsDNA in patients with Systemic lupus erythemathosus (SLE) and its relation between IgG/IgM proportion and clinical manifestations of the disease. This transversal study included 137 SLE patients according to traditional criteria (92.5% female, 79.5% Caucasian) and 58 SLE individual (93.1% female, 81% Caucasian) selected by positivity for IgG anti-dsDNA. IgG and IgM anti-dsDNA antibodies were detected by Chrithidiae luciliae indirect immunofluorescence with cut point 1/10 dilution. The presence of IgG anti-dsDNA was associated to the presence of hemolytic anemia, leukopenia/lymphopenia and Complement depletion (p<0.001). Of the 58 patients positive for IgG anti-dsDNA 15 were also positive for IgM anti-dsDNA. The group presenting both isotypes showed significant less frequency of active urinary sediment when compared to isolated IgG anti-dsDNA (6.7% versus 34.9%, p=0.046). IgG/IgM proportion distribution evidenced a trend of higher medians in the presence of arthritis and leukopenia/lymphopenia [4 (2-8) versus 1 (1-2), p=0.070 and 4 (3-8) versus 1 (1-4), p=0.066, respectively]. Summarizing, the frequency of IG anti-dsDNA was relevant in our casuistic. Positive subpopulation for both IgG/IgM isotypes anti-dsDNA was less willing to urinary sediment alterations than IgG anti-dsDNA isolated population. These data suggest a distinct biologic behavior for IgM anti-dsDNA.